2021
DOI: 10.1007/s11682-020-00424-1
|View full text |Cite
|
Sign up to set email alerts
|

Brain volumes in adults with congenital heart disease correlate with executive function abilities

Abstract: Congenital heart disease is the most common birth defect, and patients are at risk for neurodevelopmental impairment and brain abnormalities. Yet, little is known about the link between brain volumes and cognitive function in adults with congenital heart disease. Forty-four patients and 53 controls between 18 and 32 years underwent brain magnetic resonance imaging and cognitive testing, assessed with an intelligence quotient and executive function global score. Associations between brain volumes and cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 40 publications
3
25
0
Order By: Relevance
“…47,48 Interestingly, significant associations have been found between TBV and IQ, executive, and motor outcomes for school-age children, adolescents, and adults. [49][50][51][52] One reason that TBV is possibly associated with outcome in cross-sectional studies but not in longitudinal studies might be that no additional factors accumulating over time contribute to the variance in outcome.…”
Section: Discussionmentioning
confidence: 99%
“…47,48 Interestingly, significant associations have been found between TBV and IQ, executive, and motor outcomes for school-age children, adolescents, and adults. [49][50][51][52] One reason that TBV is possibly associated with outcome in cross-sectional studies but not in longitudinal studies might be that no additional factors accumulating over time contribute to the variance in outcome.…”
Section: Discussionmentioning
confidence: 99%
“…These alterations in brain volume are associated with poorer neurodevelopmental outcome in CHD patients: Studies in infants with CHD have shown that altered brain volume at infancy predicts cognitive abilities in later childhood, including intellectual function ( Meuwly et al, 2019 ) and language development ( Rollins et al, 2017 ). Several studies in adolescents and young adults with CHD demonstrated associations between lower local and total brain volume and intellectual function ( Von Rhein et al, 2014 ), working memory ( Fontes et al, 2019 , Latal et al, 2016 ), and executive function ( Naef et al, 2021 , Semmel et al, 2018 ). In addition to macroscopic alterations in brain volume, neuroimaging studies have also revealed alterations in brain microstructure in infants, children and young adults with CHD, which also appear to be linked to delayed or altered cognitive development.…”
Section: Introductionmentioning
confidence: 99%
“…Significant reductions in global brain volume and subcortical gray matter (GM) volume were associated with lower SaO 2 in our adolescent and adult Fontan cohort ( Verrall et al, 2021 ), consistent with our earlier findings from adults with other forms of cyanotic CHD ( Cordina et al, 2014 ). Smaller global brain volumes were associated with worse cognitive outcomes in our Fontan cohort ( Verrall et al, 2021 ), and other older CHD cohorts ( Naef et al, 2021 , von Rhein et al, 2014 ). Importantly, associations between hypoxemia and WM microstructure in people with a Fontan circulation and subsequent cognitive impairment have not yet been established.…”
Section: Introductionmentioning
confidence: 57%